Volume 2: Safety and Reliability; Pipeline Technology 2003
DOI: 10.1115/omae2003-37068
|View full text |Cite
|
Sign up to set email alerts
|

Lazy-Wave Steel Rigid Risers for FSO With Spread Mooring Anchoring System

Abstract: Petrobras developed projects with European companies and Brazilian universities in order to study different configurations of steel risers using flexibilization elements. For the bow turret-moored FPSOs the lazy-wave configuration was considered the most adequate due to its structural behaviour and costs when compared to other configurations. A detailed study was performed by the Petrobras R&D Center to verify the structural integrity of a lazy-wave SCR (SLWR) attached to a turret-moored FPSO at a water de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There was a work carried out at CENPES that focused in considering two peak sea states and with environmental data bringing concomitant occurrence of wave, current and wind , [12,13,14]. .…”
Section: Modifications In the Design Datamentioning
confidence: 99%
“…There was a work carried out at CENPES that focused in considering two peak sea states and with environmental data bringing concomitant occurrence of wave, current and wind , [12,13,14]. .…”
Section: Modifications In the Design Datamentioning
confidence: 99%
“…Another study performed was checking the structural integrity and feasibility of a 10.75" oil export SLWR connected to the border of a spread-moored FSO at a water depth of 1800 m. The results for the installed riser also showed its feasibility [12]. Another study performed was checking the structural integrity and feasibility of a 10.75" oil export SLWR connected to the border of a spread-moored FSO at a water depth of 1800 m. The results for the installed riser also showed its feasibility [12].…”
Section: Lazy-wave Configuration For Fpsomentioning
confidence: 99%
“…The main aspect for fatigue is that analysis results showed that buoyancy modules region was more affected by VIV that contributed to almost 90% of fatigue damage in this region, leading to an extension of strakes in top region of about 30% of riser length [12].…”
Section: Lazy-wave Configuration For Fpsomentioning
confidence: 99%
“…The geometric characteristic of the LWSCR was basically suggested to isolate the riser motion from the vessel motions through the factitious arch and sag parts. By the motion isolation effect, LWSCRs may avoid significantly large dynamic amplification (Jacob et al, 1999;Silva et al, 1999;Torres et al, 2001Torres et al, , 2002Torres et al, , 2003Li and Nquyen, 2010). Yue et al (2011) performed analytic study to compare structural performance of conventional SCR, shaped SCR, and LWSCR, which are attached to a turret moored FPSOs in 800 m water depth, West Africa, under assumed 100-yr events.…”
Section: Introductionmentioning
confidence: 97%